THE PROTECTION OF CIVILIAN IN THE ARMED CONFLICT IN THE PERSPECTIVE OF INTERNATIONAL HUMANITARIAN LAW: AN ANALYSIS ON THE ACTION OF ISLAMIC STATE OF IRAQ AND SYRIA (ISIS) IN ATTACKING THE CIVILIAN - Arum Anggraeni Maulida (FH 15 UMY 063, 2015)
*63